The Contactless Vital Sensing System Precisely Reflects R‐R Interval in Electrocardiograms of Healthy Subjects - SUGA, KENTARO; HORI, HIKARU; KATSUKI, ASUKA; OHASHI, MASAHIRO; TEZUKA, TADANORI; MATSUO, MASATOSHI; NAKAMURA, TSUYOSHI; YOSHIMURA, REIJI (Pacing and clinical electrophysiology, 2017)
Background The aim of the present study was to investigate the validity of the contactless vital sensing system that we previously developed. Methods A total of 111 healthy Japanese subjects were recruited from the University of Occupational and Environmental Health and the Panasonic Corporation AVC Networks Company. All subjects underwent an evaluation using the contactless vital sensing system and electrocardiography (ECG). We compared the R‐R interval obtained using the new contactless sensing system to that obtained using ECG. Results A very strong correlation was observed between the instruments. Conclusions This result confirms the validity of the new contactless sensing system in evaluating healthy subjects.